The Harmonic Component of the Millihertz Quasi-periodic Oscillations in 4U 1636-53 - Fei, Zhenyan (2021)
We studied the harmonics of the millihertz quasi-periodic oscillations (mHz QPOs) in the neutron star low-mass X-ray binary 4U 1636-53 using the Rossi X-ray Timing Explorer observations. We detected the harmonics of the mHz QPOs in 73 data intervals, with most of them in the transitional spectra state. We found that the ratio between the rms amplitude of the harmonic and that of the fundamental remains constant in a wide range of the fundamental frequency. More importantly, we studied, for the first time, the rms amplitude of the harmonics versus energy in 4U 1636-53 in the 2-5 keV range. We found that the rms amplitude of both the harmonic and the fundamental shows a decreasing trend as the energy increases, which is different from the behaviors reported in QPOs in certain black hole systems. Furthermore, our results suggest that not all observations with mHz QPOs have the harmonic component, although the reason behind this is still unclear.